2017
DOI: 10.3389/fneur.2017.00576
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Transcranial Direct Current Stimulation, Transcranial Pulsed Current Stimulation, and Their Combination on Brain Oscillations in Patients with Chronic Visceral Pain: A Pilot Crossover Randomized Controlled Study

Abstract: ObjectiveChronic visceral pain (CVP) syndromes are persistently painful disorders with a remarkable lack of effective treatment options. This study aimed at evaluating the effects of different neuromodulation techniques in patients with CVP on cortical activity, through electreocephalography (EEG) and on pain perception, through clinical tests.DesignA pilot crossover randomized controlled study.SettingsOut-patient.SubjectsAdults with CVP (>3 months).MethodsParticipants received four interventions in a randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 52 publications
(60 reference statements)
0
27
1
Order By: Relevance
“…Reproducibility of the results is paramount and there must be a clear description of the protocol used for the interventions (Brunoni et al, 2012). Montages with anode and cathode positions (including number of respective electrodes) (Nasseri et al, 2015), how this montage was determined (measurements, neuro-navigation), size and shape of electrodes (rectangular, circular or EEG type), current intensity, duration, number of sessions and interval between sessions (Thibaut et al, 2017) are extremely important parameters that need to be made explicit (Pinto et al, 2018). For tACS, a particularly vexing problem for the field has been the confusion between peak-to-peak and true (baseline-topeak) amplitude.…”
Section: Reporting Tes Specificationsmentioning
confidence: 99%
“…Reproducibility of the results is paramount and there must be a clear description of the protocol used for the interventions (Brunoni et al, 2012). Montages with anode and cathode positions (including number of respective electrodes) (Nasseri et al, 2015), how this montage was determined (measurements, neuro-navigation), size and shape of electrodes (rectangular, circular or EEG type), current intensity, duration, number of sessions and interval between sessions (Thibaut et al, 2017) are extremely important parameters that need to be made explicit (Pinto et al, 2018). For tACS, a particularly vexing problem for the field has been the confusion between peak-to-peak and true (baseline-topeak) amplitude.…”
Section: Reporting Tes Specificationsmentioning
confidence: 99%
“…Such heterogeneity may be explained by single site stimulation and therefore an inability to produce a meaningful whole brain effect. Following this rationale, in a recent study [43], the fronto-parietal network was stimulated using tDCS. However, results showed that only 30% of MCS patients positively responded to stimulation.…”
Section: Potential Therapeutic Interventionsmentioning
confidence: 99%
“…However, results showed that only 30% of MCS patients positively responded to stimulation. Crucially, in this study the stimulation targets were not chosen based on functional connectivity maps [43].…”
Section: Potential Therapeutic Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these samples did not include severe SCP children of GMFCS levels III-V. To our knowledge, there is only one NIBS study involving children with spastic quadriplegia [15] in which high frequency (5 Hz) repetitive transcranial magnetic stimulation (rTMS) was used to treat upper limb spasticity; however, measured outcomes using Ashworth scale tests failed to reach significance. Moreover, there are no studies that have investigated the effects of NIBS on lower limb spasticity in children with SCP in GMFCS levels III-V. Transcranial pulsed current stimulation (tPCS) is a novel type of NIBS that has recently gained increasing attention in experimental settings [16][17][18][19][20][21][22][23][24][25][26], delivering pulsed currents at a predetermined frequency to the cortex, as opposed to the direct current provided by tDCS. While there are yet no studies done involving tPCS and children with SCP, the safety of tPCS had been investigated in the treatment of Parkinson's disease, with no adverse events recorded, and post-treatment results showed significant improvement in gait and balance [27].…”
Section: Introductionmentioning
confidence: 99%